2017
DOI: 10.1111/ijac.12811
|View full text |Cite
|
Sign up to set email alerts
|

Glass ceramics sealants for SOFC interconnects based on a high chromium sinter alloy

Abstract: The operation of solid oxide fuel cells requires gas tight and stable sealing materials. Glass ceramic materials have been established to seal different stack designs and can be optimized to match the requirements of components and joining conditions. It is known that glass based sealants are sensitive to the formation of undesired chromia species in contact with ferritic steels used as interconnects. Their formation depends on the earth alkaline type and content in the glass as well as the chromium content of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This study was conducted on a commercial barium alumino borosilicate glass used for SOFC sealing (K01, KERAFOL keramische Folien GmbH, Eschenbach, Germany; also supplied by Fraunhofer IKTS, Dresden, Germany [ 7 ] ). The glass transition temperature, T g = 649 °C, and the coefficient of thermal expansion, CTE 25−400 °C = 7.6 · 10 −6 K −1 , were measured in the study by Agea‐Blanco et al [ 24 ] No crystallization during heating could be detected by DTA, as also reported in the study by Agea‐Blanco et al [ 24 ] for the glass under this study.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted on a commercial barium alumino borosilicate glass used for SOFC sealing (K01, KERAFOL keramische Folien GmbH, Eschenbach, Germany; also supplied by Fraunhofer IKTS, Dresden, Germany [ 7 ] ). The glass transition temperature, T g = 649 °C, and the coefficient of thermal expansion, CTE 25−400 °C = 7.6 · 10 −6 K −1 , were measured in the study by Agea‐Blanco et al [ 24 ] No crystallization during heating could be detected by DTA, as also reported in the study by Agea‐Blanco et al [ 24 ] for the glass under this study.…”
Section: Methodsmentioning
confidence: 99%
“…Further details about the crystalline phases will be discussed in the later sections of this article. Nevertheless, the CTE of HJ28 glass-ceramic is matching with CTEs of other cell components i.e., Crofer22APU (12 × 10 −6 K −1 ) and 3YSZ (10.5 × 10 −6 K −1 ), [7,31] and is suitable for the SOEC applications.…”
Section: Thermal Analysismentioning
confidence: 97%
“…Many researchers 160–176 have investigated the crystallization of CAS (CaO‐Al 2 O 3 ‐SiO 2 ) glasses. CaO‐based borosilicate glasses have high CTE than BaO‐ and SrO‐based glasses 169 .…”
Section: Effect Of Different Glass Constituents On Sealing Propertiesmentioning
confidence: 99%
“…31 However, the BaO-containing glass sealant required high temperature for sealing to achieve proper gas tightness due to its higher crystallization rate with high viscosity and poor wettability to adhere with interconnecting materials. 31 CaO-containing glasses Many researchers [160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176] have investigated the crystallization of CAS (CaO-Al 2 O 3 -SiO 2 ) glasses. CaO-based borosilicate glasses have high CTE than BaO-and SrO-based glasses.…”
mentioning
confidence: 99%